Calcareous nannofloras in Western Lobe Offshore, Niger Delta : eutrophication and climate change implications - Oretade, Bamidele Samuel; Che Aziz Ali, (Penerbit Universiti Kebangsaan Malaysia, 2021)
In support of the on-going temporal palaeoenvironmental and palaeoclimatic reconstructions of the Neogene sediments, this study attempts describing the palaeo-proxies recovered from DEL-1 Well, western offshore Niger Delta. The use of standard smear slide method enabled the recovery of well-preserved calcareous nannofossils that depicts early to mid – Miocene (NN4 – NN5) sediments. The up-hole relationships between the relative abundance of Discoaster spp. and coccolith size of Reticulofenestra show step by step collapse of sea surface stability from early to middle Miocene. The lower horizons (8000-9460 ft.) exhibit relatively high Discoaster abundance and relatively large Reticulofenestra spp. size to suggest a deep thermocline and nutricline that characterize oligotrophic conditions in less warm-water induced climate. Conversely, upper horizons (5225-6550 ft.) exhibit significant changes with relatively low abundance of Discoaster spp. and relative small Reticulofenestra spp. size to suggest a shallow thermocline and nutricline that characterize eutrophic conditions in warm-water induced climate. The high abundance of Helicosphaera coccoliths (Helicosphaera carteri) within the mid - NN5, suggests mesotrophic conditions within a stressed environment (fluctuating salinity and terrigenous influx) with the occurrence of carbonate fluctuating event. The combined parameters indicate gradual eutrophication and collapse of sea surface stability in favour of nutrients and influx of fluvial mechanism (terrestrial input) in the ocean water as it progressed from early to middle Miocene. The palaeo-proxies assemblages depict hyposaline waters in a neritic environment, characterized with induced warm water climatic conditions.